PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA KELAS XI MIA SMA N 1 BANGUN PURBA TAHUN PEMBELAJARAN 2014/2015 - Sari, Nirmala; Lestari, Rena; -, Dahlia (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aim of this study was to determine the effect of cooperative learning model of type Student Team Achievement Division (STAD) assisted the picture media towards process science skills and learning results of students at class XI MIA SMA N 1 Bangun Purba in Academic Year 2014/2015. This study used quasi-experimental. Based on the results obtained in the experimental class average value of process science skills of observation is 79,60 with a high criteria. The results of hypothesis testing obtained ttest>ttable (2.859>2.064) can be conclude that cooperative learning model of type STAD assisted the picture media effect the process science skills and learning results of students at class XI MIA SMA N 1 Bangun Purba in Academic Year 2014/2015.